(untitled) (World Science, 2018)
The article deals with the writings by Dmytro Chub, who is one of the prominent representatives of the Australian Diaspora branch in the children’s literature. The issues of the Other in his writings are defined as an uninhabited space, which emigrant develops. Australia is defined in author’s writings as “new acquired motherland”.